ANALIS RESPONSE TIME REPLIKASI DATABASE SISTEM INFOMASI INVENTORI DARAH - Kusuma, Abdi Pandu; Huda, Miftahul; Santi, Indyah Hartami (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
This study aims to find out analsis response time replication of two-way database on blood inventory system in Madiun residency: Madiun City, Madiun Regency and Ponorogo Regency. Thepreviously used system has been integrated using a one-way database replication with centralizeddatabase system, but in the course of its journey found the instability of centralized databasesystem, such as the delay between 2-4 seconds during query activity and the data that does not gointo the data center when do activities. The method used in this research is to use the method ofcomparison between one-way replication system with two-way replication system. The data madefor comparative analysis are CPU response time, trougput, delay and packet loos network at eachUTD in Madiun residency. The tools used to get data using Mary DB and wireshark software. Theresults of the research indicate that the two-way database replication system in Madiun andMadiun City shows better CPU response time, troughput, delay and packet loss compared to theprevious system, only Ponorogo has decreased performance compared to the old system.Keywords: Blood inventory system, two-way data base replication, CPU response time, delay, packet loss, throughput.